Experience curves as a planning tool. Part 2. Pyrrhic victories and practical problems - Cedric G. Robinson (South African Journal of Business Management, 1982)
Strategies based on the experience curve effect require that predatory price cutting leads to enhanced market share and an increasingly competitive cost structure vis-à-vis the competition. The company that rides the experience curve to the bank has cost advantages, pricing discretion and reaps handsome profits. Corporate graveyards are littered with the corpses of companies who have adopted too naive an approach to, and too simplistic an acceptance of, the concepts first pioneered by the Boston Consulting Group. This, the second of two articles on the experience curve, highlights pyrrhic victories in the quest for market share and asks six key questions that need to be answered before adopting an experience-driven strategy. Likewise 12 problem areas in the application of this approach are identified.
Keywords: 650